Subacute oral toxicity study of sesamol in Wistar albino rats - Gopika, R; Bibu, John Kariyil; Archana, Raj; Aiswaria, Das; Sona, Shaji; Anoopraj, R (Plant Science Today, 2026)
Sesamol, a natural phenolic compound predominantly found in sesame oil, has attracted considerable research interest for its potent antioxidant activity and additional anti-inflammatory and anticancer effects, positioning it as a promising candidate for preventing and managing oxidative stress-related conditions and other therapeutic applications. The present study was undertaken to evaluate the subacute oral toxicity of sesamol in Wistar albino rats, thereby establishing its safety profile under repeated exposure. Following Organisation for Economic Co-operation and Development (OECD) guideline 407, the rats were administered daily with oral doses of sesamol at doses of 26 mg/kg, 130 mg/kg and 650 mg/kg for 28 days, with inclusion of satellite groups to evaluate the reversibility of potential toxic effects. Haematological, biochemical, organ weight, clinical signs, feed, water intake and histopathological parameters were observed throughout the study. High-dose treated animals showed increased water intake. Biochemical studies showed elevation in alanine aminotransferase (ALT) in the high-dose treated group and satellite groups showed mild hepatic injury, while cholesterol and creatinine remained normal. Haematological studies showed reduced haemoglobin in the satellite high-dose treated group and decreased lymphocytes and monocytes in medium and high-dose treated groups, indicating possible myelosuppression. Liver histology revealed minimal dose-dependent steatosis at 130 mg/kg, mild at 650 mg/kg and partial recovery in satellite groups. No lesions were observed in the brain, kidney, heart, reproductive organs, or other tissues. In silico docking studies revealed that sesamol showed binding affinity to CYP1A2 (-6.5 kcal/mol) and CYP3A4 (-5.9 kcal/mol), suggesting possible interaction with drug-metabolising enzymes contributing to hepatotoxicity at higher doses. Sesamol was well tolerated at low and medium doses (26 and 130 mg/kg) without observed adverse effects, while the high dose (650 mg/kg) induced mild hepatotoxic and haematological changes. The no observed adverse effect level (NOAEL), lowest observed adverse effect level (LOAEL) and maximum tolerated dose (MTD) were determined as 130, 650 and 650 mg/kg per day respectively. These findings supported the safe use of sesamol at appropriate doses while emphasising the need for further evaluation of chronic toxicity, genotoxicity and mechanisms of toxicity.